Magnetic resonance imaging surrogates of molecular subgroups in atypical teratoid/rhabdoid tumor - Nowak, Johannes; Johann, Pascal-David; Kool, Marcel (Neuro-Oncology, 2018)
Abstract: Background. Recently, 3 molecular subgroups of atypical teratoid/rhabdoid tumor (ATRT) were identified, but little is known of their clinical and magnetic resonance imaging (MRI) characteristics. Methods. A total of 43 patients with known molecular subgroup status (ATRT–sonic hedgehog [SHH], n = 17; ATRT-tyrosine [TYR], n = 16; ATRT–myelocytomatosis oncogene [MYC], n = 10) were retrieved from the EU-RHAB Registry and analyzed for clinical and MRI features. Results. On MRI review, differences in preferential tumor location were confirmed, with ATRT-TYR being predominantly located infratentorially (P < 0.05). Peritumoral edema was more pronounced in ATRT-MYC compared with ATRT-SHH (P < 0.05) and ATRT-TYR (P < 0.05). Conversely, peripheral tumor cysts were found more frequently in ATRT-SHH (71%) and ATRT-TYR (94%) compared with ATRT-MYC (40%, P < 0.05). Contrast enhancement was absent in 29% of ATRT-SHH (0% of ATRT-TYR; 10% of ATRT-MYC; P < 0.05), and there was a trend toward strong contrast enhancement in ATRT-TYR and ATRT-MYC. We found the characteristic (bandlike) enhancement in 28% of ATRT as well as restricted diffusion in the majority of tumors. A midline/off-midline location in the posterior fossa was also not subgroup specific. Visible meningeal spread (M2) at diagnosis was rare throughout all subgroups. Conclusion. These exploratory findings suggest that MRI features vary across the 3 molecular subgroups of ATRT. Within future prospective trials, MRI may aid diagnosis and treatment stratification
Advance access date 13 July 2018
Gesehen am 06.02.2020